Flipped classroom and Project Based Learning in Biology classroom: an innovation project for 1.º of eso. Experience assessment - Noelia SÁNCHEZ SÁNCHEZ (Enseñanza & Teaching, 2018)
The present article takes as a target to value the development of a didactic proposal for the Biology and Geology subject of 1st of eso. This proposal is based on flipped classroom (fc) and project based learning (pbl) methodologies and it centers on the development of the teaching-learning process of the anatomical and physiological characteristics of the different living beings included inside the so called Five Kingdoms. The fc is a pedagogic model that transfers the work of certain learning processes out of the classroom and uses the class time together with the experience of the teacher, to facilitate and to promote other processes of acquisition and practice of knowledge inside the classroom. Likewise, in the pbl model are the pupils those who set the rhythm for advancing in the acquisition of new knowledge, promoting the necessary thinking skills for a significant learning. Therefore both methodologies present themselves as a good option to conteract the problems associated with traditional Science education.